Mechanics of Biological Systems, Materials and other topics in Experimental and Applied Mechanics, Volume 4 Proceedings of the 2017 Annual Conference on Experimental and Applied Mechanics (Conference Proceedings of the Society for Experimental Mechanics Series,, 2018)
Mechanics of Biological Systems, Materials and other topics in Experimental and Applied Mechanics, Volume 4 of the Proceedings of the 2017 SEM Annual Conference & Exposition on Experimental and Applied Mechanics, the fourth volume of nine from the Conference, brings together contributions to important areas of research and engineering. The collection presents early findings and case studies on a wide range of topics, including: Biological & Biomimetic Materials Cell Mechanics & Traumatic Brain Injury Mechanics of Collagen & Other Proteins Force Generation in Biological Machinery Education & Research in Progress Applications.